2022
DOI: 10.3390/ijms231710193
|View full text |Cite
|
Sign up to set email alerts
|

From Double-Strand Break Recognition to Cell-Cycle Checkpoint Activation: High Content and Resolution Image Cytometry Unmasks 53BP1 Multiple Roles in DNA Damage Response and p53 Action

Abstract: 53BP1 protein has been isolated in-vitro as a putative p53 interactor. From the discovery of its engagement in the DNA-Damage Response (DDR), its role in sustaining the activity of the p53-regulated transcriptional program has been frequently under-evaluated, even in the case of a specific response to numerous DNA Double-Strand Breaks (DSBs), i.e., exposure to ionizing radiation. The localization of 53BP1 protein constitutes a key to decipher the network of activities exerted in response to stress. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…Much evidence has shown that 53BP1 sustains the p53 activity in the cell fate decision [16][17][18][19][20] as a complementary function to its well-known role in DNA Damage Recognition and Response (DDR). To investigate if 53BP1 directly participates in p53 transactivation activity, we first employed an image-cytometry pipeline to quantitatively analyze the relationships between p53 content, IR-induced foci and DDR kinetics, and transcriptional activity measured by the amount of RNA Polymerase II phosphorylated on Serine 5 (Pol II-S5p), a marker of transcriptional initiation.…”
Section: Multivariate Quantitative Analysis Of P53 53bp1 and Transcri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Much evidence has shown that 53BP1 sustains the p53 activity in the cell fate decision [16][17][18][19][20] as a complementary function to its well-known role in DNA Damage Recognition and Response (DDR). To investigate if 53BP1 directly participates in p53 transactivation activity, we first employed an image-cytometry pipeline to quantitatively analyze the relationships between p53 content, IR-induced foci and DDR kinetics, and transcriptional activity measured by the amount of RNA Polymerase II phosphorylated on Serine 5 (Pol II-S5p), a marker of transcriptional initiation.…”
Section: Multivariate Quantitative Analysis Of P53 53bp1 and Transcri...mentioning
confidence: 99%
“…However, many published papers shed light on the novel functions of 53BP1, linking in vivo 53BP1 protein to the p53-driven transcriptional program that determines cell fate [16][17][18][19]. In recent work, we applied automated image cytometry and correlative super-resolution microscopy to study the spatio-temporal dynamics of p53-53BP1 interaction following severe DNA damage by Ionizing Radiation [20]. Both spatial compartmentalization, with the formation of the putative p53-53BP1 complex out of the IR-induced γH2A.X foci, and temporal localization, with the detection of maximum interaction at late time points after irradiation when p53 was stabilized and damage foci reduced by the DNA-repair activity, suggested that 53BP1 can work to sustain the p53-controlled transcriptional program.…”
Section: Introductionmentioning
confidence: 99%
“…Several pieces of evidence showed a large panel of interactors revealing novel putative functions that go beyond 53BP1's role in damage recognition and DNA repair [39][40][41][42][43][44][45]. Recent publications [36] showed how 53BP1 localization can modulate a functional switch between a classical involvement in DDR and support to p53 activity by moving from DNA Damage foci to the nucleoplasm. Consequently, it becomes of paramount importance to shed light on the structure-function relationships of this protein and its molecular partners, associating a precise measurement of the number of molecules in the cell to their intracellular localization and understanding how these parameters can vary according to the cell state (e.g., cell cycle localization).…”
Section: Application Of a Multi-modal Correlative Pipeline Step 1: Hi...mentioning
confidence: 99%
“…Automated microscopy for image cytometry provides another example of how this goal can be achieved [24,34,35]. High-resolution widefield microscopy can supply quantitative and "temporal" information, both at cellular and intracellular resolutions, to study selected phenotypes with high statistical sampling and sensitivity, e.g., the expression of molecular markers to activate cell-cycle checkpoints in response to external insults [36]. Simultaneously, as frequently observed in correlative studies between fluorescence and EM, the measured data can redirect a second 3D highresolution analysis on targeted single cells by confocal microscopy revealing novel regulatory mechanisms based on the spatial and temporal re-localization of the involved proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, this Special Issue reports experimental and theoretical works on the effects of ionizing radiation at the DNA level, as well as possible applications in cancer therapy and space radiation protection. More specifically, the work by Faretta and co-workers [ 9 ] deals with the role played by 53BP1, with respect to DNA damage response (DDR) and p53 action. Since the localization of the 53BP1 protein represents the key to deciphering the network of activities exerted in response to stress, the authors present an automated microscopy strategy for an image cytometry protocol to analyze the evolution of DDR, as well as to demonstrate how 53BP1 moves from damaged sites to the nucleoplasm, interacting with p53 and enhancing its transcriptional regulation.…”
mentioning
confidence: 99%